PROGRESSIVE IDEAS IN UPDATING TEACHER TRAINING IN DEVELOPED COUNTRIES - Pazyura, Nataliya (Proceedings of National Aviation University (archive), 2015)
The article presents the results of comparative pedagogical analysis of the peculiarities of teacher training, ensuring highly professional activity of teachers in some developed countries. Especially urgent question is the updating the contents of education in higher educational institutions according to the principles of personality-oriented approach targeted at development of teachers’ personality, their common and professional competence. It is directed at revealing progressive ideas in teachers’ professional development, the role of cooperation between universities, schools and teacher professional organizations. Special attention is paid to the strengthening practical component in curriculum in the process acquirement of theoretical and practical knowledge and skills.